Comunidades pescadoras, extractivismo y la FAO. De la sabiduría del XIX a la ciencia del XXI - Xabier Brisset Martín (Cahiers de Civilisation Espagnole Contemporaine)
At the end of the 19th century, the traditional Galician fishing culture, defender of self-regulation, was challenged by the extractivist culture in favour of unlimited fishing freedom. Two antagonistic worldviews: Feeling an integral part of nature or having it as something separate. Both combined arguments with pressure measures and sought the favour of legislators to prevail in the conflict. This traumatic transition from traditional to extractivist lasted for thirty-three years. Here we will only see the first six, between 1883 and 1889. In this paper we will learn about the proposals and attitudes of both opponents and their reflection in the legislation generated in that period. We will analyse all of this in light of current scientific criteria, using as a reference the «Code of Conduct for responsible fishing» that, in defence of biodiversity and guaranteeing access to food, the FAO approved in 1995 with the endorsement of the scientific community. Thus, we will confirm the degree of confrontation or similarity of each of the options of the 19th century with the responsible fishing of the 21st.